1990
DOI: 10.1007/bf00589107
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of cerebral lesions in children with congenital hemiplegia

Abstract: This study has analysed the results of CT scans of the brains in children with congenital hemiplegia. The material consists of 111 out of a total of 151 children with this cerebral palsy syndrome in a population-based series. We have classified the morphological findings in five groups. The groups are designed to reflect the phase of maturation of the brain when the insult happened. The groups are: 1. Maldevelopment, 2. Periventricular atrophy, 3. Cortical-/subcortical atrophy, 4. Miscellaneous, 5. Normal. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
0
3

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 52 publications
5
48
0
3
Order By: Relevance
“…Studies conducted by Wiklund et al 17 showed that 17% of the CP-H cases had CNS-MF. Some reports give great importance to the presence of physical malformations outside the CNS because they indicate the occurrence of a lesion and therefore the period can be defined 1,3,4,11 .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Studies conducted by Wiklund et al 17 showed that 17% of the CP-H cases had CNS-MF. Some reports give great importance to the presence of physical malformations outside the CNS because they indicate the occurrence of a lesion and therefore the period can be defined 1,3,4,11 .…”
Section: Discussionmentioning
confidence: 98%
“…Although great progress has been achieved in relation to imaging in CP-H, 8% to 24% of the exams are reported as normal 15,17,21 . In the present study, the CT exam was normal in 18% of the cases and the MRI in 7% of the cases, demonstrating that MRI is a more efficient tool in the neroimaging evaluation of PC-H.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although MRI is known to display a greater sensitivity, 22 CT is considered an adequate imaging modality for corticalsubcortical lesions in the territory of the middle cerebral artery. 23 As such, these imaging data were retained. Patients' age at the time of the scan ranged from 5 days to 15 years with a mean of 5 years 7 months (SD 4 years 6 months).…”
Section: 2mentioning
confidence: 99%